2018
DOI: 10.29333/ejmste/94733
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Science Interest, Attitude, and Self-Efficacy of Qatari Students at the Preparatory, Secondary, and University Levels

Abstract: A large sample (n = 1,799) of Qatari female and male students at the preparatory, secondary, and university levels responded to Likert items about their interest, attitude, and self-efficacy regarding science. The items were similar to those of TIMSS and PISA, but improved upon them in several ways. The findings suggest that Qatari students are positive in their interest, attitude, and self-efficacy, but not as positive as TIMSS and PISA report. The findings raise an important question: If the students' intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Qatari students' Interest in, and Attitudes towards, Science (QIAS) project: In this project, 1,800 Qatari students at the preparatory, secondary, and university levels were surveyed about their interests, attitudes, and self-efficacy regarding science. Findings (Said, Al-Emadi, Friesen, & Adam, 2018) suggest that while Qatari students are positive in their interests, attitudes, and self-efficacy, they do not translate to outcomes in TIMSS and PISA reports, and there exists no statistically significant difference in these variables between male and female students; additionally, the findings indicated that science career interest was particularly low among female students. The findings raised two questions: first, if the students' interest, attitude, and self-efficacy are positive, then why do students have relatively low achievement scores on TIMSS and PISA?…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Qatari students' Interest in, and Attitudes towards, Science (QIAS) project: In this project, 1,800 Qatari students at the preparatory, secondary, and university levels were surveyed about their interests, attitudes, and self-efficacy regarding science. Findings (Said, Al-Emadi, Friesen, & Adam, 2018) suggest that while Qatari students are positive in their interests, attitudes, and self-efficacy, they do not translate to outcomes in TIMSS and PISA reports, and there exists no statistically significant difference in these variables between male and female students; additionally, the findings indicated that science career interest was particularly low among female students. The findings raised two questions: first, if the students' interest, attitude, and self-efficacy are positive, then why do students have relatively low achievement scores on TIMSS and PISA?…”
Section: Introductionmentioning
confidence: 82%
“…Both TIMMS and PISA reported that on their indices of "enjoyment of learning science" Qatari students scored significantly above the international average (Martin et al 2016 andOECD, 2016b). However, significant differences were not observed between the two genders in interest and attitude toward science during two longitudinal studies conducted among all students in Qatar from primary to university level (Said, Summers, Abd-el-Khalik & Wang, 2016b;Said, Al-Emadi, Friesen & Adam, 2018). BouJaouda and Gholam (2013) found that in the Arab world in general, due to sociocultural factors, girls are less likely to aspire to a STEM career than boys, while Abdulwahed, Ghani, Hasna and Hamouda (2013), and Sellami, Kimmel, Wittrock, Hunscher, Cotter and Al-Emadi (2017) found the opposite in Qatar, where girls' aspiration is significantly higher than that of boys.…”
Section: Introductionmentioning
confidence: 99%
“…Equipped with creativity, university graduates are expected to be ready to be competitive in the work field and survive the 21 st -century challenges. In addition to creativity, university students also need to arm themselves with other 21st century skills namely critical thinking (Butler, Pentoney, & Bong, 2017;Zubaidah, Mahanal, Rosyida, Lutfi, Sholihah, & Ismirawati, 2018;), creative thinking (Ersoy & Başer, 2014;Fuad et al, 2017;Yusnaeni et al, 2017), communication skills (Taveira-Gomes, Mota-Cardoso, Figueiredo-Braga, 2016;Yusof & Halim, 2014), and behavioral skills (Said, Al-emadi, Friesen, & Adam, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy is a person's belief in understanding and solving problems based on their potential, leading to successful outcomes (Said et al, 2018;Tezer et al, 2019;Unrau et al, 2018). Another definition related to self-efficacy, namely, is the belief of a person using their ability to solve problems using certain means (Šorgo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%